Naključno gibanje delcev na nihajoči membrani v Chladnijevem poskusu - Grabec, Igor (Obzornik za matematiko in fiziko, 2017)
Bouncing of marble sand particles on a vibrating membrane of a Chladni experiment is statistically characterized in the article. Records of trajectories reveal that bounces are circularly distributed and random. The mean length of their horizontal displacement is approximately proportional to the vibration amplitude above the critical level and amounts about one fourth of the corresponding jump height. The horizontal drifting of particles is described by a model of vibration driven random walk. Numerically simulated examples yield a good agreement with experimental data.
Keywords: fizika; gibanje